Study guides

☆☆

Q: 3x2 plus 2x2 plus 3 simplified?

Write your answer...

Submit

Still have questions?

Related questions

(x -3)(2x2 + 3x - 4)

3

The sum 6 (3x^2) + 8x -3 plus 3 (3x^2) - 7x + 2 = 27 x^2 + x -1

x2+7x=-2x2+6 3x2+7x-6=0 (3x-2)(x+3)=0 3x-2=0 or x+3=0 x=2/3 or x=-3

3x2 + 10x + 3 = (x + 3)(3x + 1).

-8x + 3x2 - 3

3x2 + 9x 3x(x + 3) -------------

3x2 + 48 + 192 = 3x2 + 240 = 3 (x2+ 80)

2x2 + 5x - 3 (2x - 1)(x + 3)

2x2+5x+3 = (2x+3)(x+1) when factored

3x2 + 36x + 81 = 3(x2 + 13x + 27)

3x2 + 2x + 3 + x2 + x + 1 = 4x 2+ 3x + 4

It is: 3x2-5x-2 = 0 and the value of x is -1/3 or 2 when solved

2x2+13x+15 = (2x+3)(x+5)

d/dx 2x2+3x+7=4x+3

x3 - 3x2 + x - 3 = (x2 +1)( x - 3)

x3 - 3x2 + x - 3 = (x - 3)(x2 + 1)

x2 plus 6x-2 equal -2x2 plus x ..=7x equal -3x2 ..4x=2x=2 answer ..check it if u dont want to trust ..Improved Answer:x2+6x-2 = -2x2+xx2+2x2+6x-x-2 = 03x2+5x-2 = 0(3x-1)(x+2) = 0x = 1/3 or x = -2The answer can be checked by using the quadratic equation formula.

two complex

two negative

2x2 + 11x + 15 = (x + 3)(2x + 5).

3x2 + 33x + 54 =3(x2 + 11x + 18) = 3(x + 9)(x + 2)

(2x + 1)(x + 3)

In general, no.

x2(x + 3)